Livestreaming content: strategic approach that enhance engagement and traction among Xiao Hong Shu consumers in Malaysia - Kong, Adeline Qing Qing (2024)
Using the Uses and Gratifications Theory (UGT), this study examines the factors driving consumer engagement and traction in livestreaming among Malaysian Xiao Hong Shu users. The study looks at six important factors that includes authenticity of conversation, platform selection, enjoyment, pass time, promotion and influencer. Promotion, and influencer had less of an impact than authenticity of conversation, platform selection, enjoyment, pass time with consumer engagement, according to a quantitative technique using questionnaire that involved a poll of 468 respondents. The results offer useful implications for marketers looking to maximize livestreaming tactics, as well as theoretical advances in UGT applications to digital commerce. Thus, the conclusion of this study encourages the creation of entertaining, interactive, and captivating livestream content that is aimed at improving customer behavior and brand engagement.